The effect of organizational commitment and Cost management knowledge on the relationship between budget participation and managerial performance - Laras Dwi Novlina; Mirna Indriani; Indayani indayani (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
The purpose of this study is to examine the effect of organizational commitment and cost management knowledge on the relationship between budget participation and managerial performance. The data used in this study collected by distributed questionnaires to 700 managers work in manufacturing companies in Indonesia. The sample used in this study consists of 98 managers who involve in budgetary participation. Data were analyzed by using the Structural Equation Model (SEM) based Partial Least Square (PLS) with WarpPLS 6.0 software. The result of this study represent that budgetary participation has a positive effect on managerial performance and cost management knowledge moderate the relationship between budgetary participation and managerial performance, while organizational commitment has no effect on the relationship between budgetary participation and managerial performance.